Safety and Efficacy of Direct-Acting Antivirals in the Treatment of Hepatitis C in Transplant Recipients - Hyppolito, Elodie Bomfim; Pires Neto, Roberto da Justa; Teixeira , Larissa Peixoto; Marques, Lara Martins Sampaio; Alencar, Vitória Bezerra de; Pereira, Karla Brandão; Linhares, Lívia Melo Carone; Araújo Filho, Antônio Haroldo; Viana, Cyntia Ferreira Gomes; Rocha, Tarciso Daniel dos Santos; et al. (Brazilian Journal of Transplantation, 2025)
Objectives: To perform a comparative analysis, evaluating the efficacy and safety profiles discerningly in a cohort of liver transplant recipients and non-liver transplant recipients infected with hepatitis C and treated with direct-acting antivirals (DAA). Methods: This study is a real-life retrospective, observational analysis of individuals with chronic hepatitis C who were treated with DAA. During this period, 990 patients diagnosed with hepatitis C received DAA therapy, 165 of whom had undergone liver transplantation. Exclusion criteria included HIV-positive patients and those without a sustained virologic response (SVR) assessment. Results: The SVR was 95.8 and 95.6% in liver transplant recipients and nonrecipients, respectively (p = 0.94). The majority of patients were treated with sofosbuvir (SOF) in combination with daclatasvir, simeprevir, and ledipasvir. Ribavirin (RBV) was co-administered to 43.2% of patients, resulting in no improvement in SVR and an increase in adverse events. Treatment of genotype 2 patients with SOF and RBV and genotype 3 patients with SOF, interferon, and RBV for only 12 weeks showed suboptimal efficacy (89.5 and 83.3%), respectively. Conclusion: The treatment of hepatitis C with DAA is as effective and safe in liver transplant patients as in non-liver transplant patients, and the prescription of RBV is inadvisable due to the increase in serious adverse events without improvement in SVR.